A novel posterior endoscopic cervical approach for treating cervical spondylotic radiculopathy: a finite-element analysis(C2-T1) - Lei, Bo; Qin, Chaofan; Cheng, Si; Yu, Qingshuai; Liu, Jiming; Wang, Xin; Hu, Tao; Ma, Ke; Chen, Yu; Yan, Zhengjian (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study aimed to preliminarily demonstrate the safety of using a novel surgical approach and investigate the biomechanical effects of different surgical approaches on the cervical spine.MethodsA finite-element model of an intact C2–T1 cervical spine was established. Different posterior endoscopic cervical discectomy (PECD) surgical approach models were constructed based on the intact model. The T1 inferior end was fully fixed, and a 100-N compressive load was applied to the odontoid process to simulate the head weight. A 2.0 Nm moment was applied to the odontoid process in three anatomical planes to simulate flexion-extension, lateral bending toward the surgical side, and rotation toward the surgical side. The range of motion (ROM), C6 pedicle stress, C6 facet joint stress, and intervertebral disk stress were calculated under different loading conditions.ResultsThe finite-element simulations revealed that 1. Conventional PECD resulted in ROM changes within 5%, while the novel approach led to ROM variations depending on the bone tunnel preparation and motion type, with a maximum increase of 7.4%. 2. The novel approach altered C6 pedicle stress, with peak stress reaching 66.6 MPa (5.4 times the normal maximum), whereas conventional PECD had negligible effects on pedicle stress. 3. Conventional l PECD increased facet joint stress by up to 10.2%, whereas the novel approach changed it within 6.6%. 4. Both approaches caused less than a 5% change in intervertebral disk pressure.ConclusionThis study preliminarily demonstrates that the novel surgical approach is safe, with daily activity loads unlikely to cause fractures in the lateral mass or pedicle. Compared to the intact model, neither approach significantly affected the cervical ROM or disk pressure. Additionally, the novel approach had a lesser impact on facet joints, suggesting it may be a potentially advantageous option for PECD. Based on the pedicle stress and ROM changes, preserving the inferomedial quarter of the pedicle is beneficial, and minimizing structural disruption while effectively decompressing the nerve root should be prioritized.